Civic Education in Sri Lanka - National Education Research and Evaluation Centre, University of Colombo (University of Colombo, 2012)
Civic Education in Sri Lanka The research study on Civic Education – Sri Lanka (CESL) was conducted in 2003 to assess the status of democratic and civic competencies of students completing Grade 9 in the school system, to inform the development of a comprehensive long-term program to promote democratic and pluralistic values through the school education system. The CESL study is based on the Civic Education Study (CIVED) conducted in 28 countries in 1998 by the International Association for the Evaluation of Educational Achievement (IEA). The national representative sample of the CESL study comprises of 133 schools, 2655 students, 265 teachers and 132 Principals of schools. The three instruments of data collection administered to students, teachers and Principals respectively were adapted and translated to Sinhala and Tamil, from the instruments used in the CivEd Study. The data is presented and analyzed using appropriate quantitative and qualitative methods. The findings of the CESL study: 1. Findings on Civic Knowledge of students 1.1 As assessed by test mean scores, in general, the achievement of Sri Lankan students in civic knowledge, content and skills is lower relative to the achievement of international students in the CIVED study. In particular, their performance is poor in items that test interpretive skills. 1.2 There are statistically significant differences in student achievement as assessed by test mean scores by the selected variables - school type, medium of instruction, gender and ethnicity; highest achievement is by the 1AB and Private schools, Sinhala medium, males, Muslims, and Buddhists respectively. 1.3 Students’ memberships and active participation in organizations is positively correlated with civic achievement scores. 1.4 Out of school variables such as home literacy, family and home environment correlate positively with mean scores; for example, more books in the home, higher parental educational qualifications, higher continuing education aspirations of students, smaller families. 1.5 There is a positive correlation of higher mean scores with reasonable amounts of time spent with friends after school and in TV/Video viewing. 2. Findings on the school and classroom context of civic knowledge The findings from reviewing the literature are that 2.1 The attempt since 1972 to impart civic education through curriculum integration has failed to bring about the expected integration and the desired learning outcomes. 2.2 The failure in translating the aims of education to contribute to the development of good citizens and caring individuals with exemplary character and values, the lack of civic and social responsibility, reflects on civic instruction in classrooms and lacunae in the curriculum and in the activities in the ‘hidden curriculum’ that pervades the social climate of the school. 2.3 A contextual basis for the identification of curriculum areas that need to be strengthened, in both coverage and in teacher training is provided by an assessment of coverage of secondary school civic related curriculum, the importance accorded by teachers to topics and, their level of confidence in teaching these topics. 2.4 The model that integrates civic education into other social sciences is the most popular among teachers, in indicating how civic education should be taught. 2.5 Teachers strongly affirm that schools are places where civic education ought to be taught and can be taught effectively and that civic education matters a great deal in facilitating students’ civic development. 2.6 Teachers believe that agreement on what is worth learning in civic education is possible but doubt societal consensus, accept official curriculum as points of orientation and are willing to negotiate with students over what is to be studied. 2.7 Teachers agree that students learn in school to understand people, to cooperate, to solve problems, to protect the environment, to develop concern about the country and to know the importance of voting. 2.8 Some teachers in Sri Lanka favor inculcating the more conventional forms of political allegiance and participation over attitudes and skills that imply a more activist stance, in the future citizens they teach. 2.9 Teachers in Sri Lanka draw both from externally generated materials such as official curriculum and textbooks and, from internally generated materials such as teachers’ own ideas and self-generated materials, in preparation for teaching. 2.10 The three need areas that teachers in Sri Lanka prioritized to improve civic related subject teaching were additional training in subject matter knowledge, in teaching methods, and better materials and textbooks. 2.11 The teaching learning methodologies used more frequently in civic education classrooms in Sri Lanka are teacher and didactic teaching focused than learner initiated and inquiry based learning focused, with interactive approaches used sparingly. However, teachers report that there is discussion of controversial issues in their civic education classrooms. 2.12 The methods of assessment used more frequently in civic education classrooms are written compositions, oral participation and multiple-choice tests. 2.13 Students are inclined towards proactive participation in school life, have very positive perceptions on their own capacity to bring about change and to democratize the way schools function. 2.14 In Sri Lanka, the participation of students in the political life of the school is minimal. However, they cooperate with teachers to solve problems of discipline, resolve problems among students, between teachers and students and, school problems in general. 2.15 Principals of schools report that negative behaviors such as truancy, bullying, vandalism and violence occur sometimes in more than half the schools in the sample. 2.16 As reported by the Principals, the school climate for learning reflected in students’ and teachers’ attitudes, and in parental involvement, is positive and supportive of academic achievement. 3. Findings on Students’ concepts of Democracy Citizenship and Government 3.1 The findings on SL students’ concepts of democracy, citizenship and government in general compare well with findings in the CIVED study and are consistent with the pattern of responses of the INT student sample. 3.2 On the concept of democracy, citizens’ freedom to express opinions, free elections, strong civil society in the form of organizations are attributes that the vast majority of SL students believe to be good for democracy; attributes that are judged to be bad for democracy are monopoly newspaper ownership, political influence in the judicial sphere, and special influence by the wealthy on the government. 3.3 On the concept of citizenship, both social movement related participation and conventional political activities are included in the SL students’ concept of good citizenship for adults, with more importance accorded to voting than to activities that imply conflict of opinions such as joining a political party ad engaging in political discussions. 3.4 On the concept of government, 14 year olds think of societal items rather than economic items as the government’s responsibility. There are signs that in Sri Lanka, with the young, the concept of an open economy is gaining ground over the strongly held protectionist affiliation to the concept of welfare state. 4. Findings on current and expected participation in political action 4.1 SL students are more interested in national than in international politics, and are more likely to discuss national and international politics with parents/family members and peers than with teachers. 4.2 The vast majority of students are familiar with the most crucial national political agenda, the peace talks and matters related. 4.3 A little over half the respondents consider themselves politically interested and knowledgeable. 4.4 Television is the media most used by students to obtain news, in preference to radio news broadcasts and the newspapers. 4.5 Other than voting in elections, the majority of SL students do not envisage more direct political participation such as contesting elections or joining a political party. They expect to participate in social movement activities, would join in non-violent protest marches, a few would engage in unconventional illegal activities, such as ‘spray painting protest slogans on walls.’ 5. Findings on trust in institutions 5.1 A relatively high percentage of SL students have trust in the government-related institutions listed. Courts and the Police are trusted the most, followed by national and local governments. Political parties are trusted very little. 5.2 A comparison with the findings of the National Youth Survey indicates that as they grow older youth in Sri Lanka lose some of the trust they had in these institutions at fourteen years of age. 5.3 Students in Sri Lanka have a sense of trust or attachment to the country as a political community and a positive sense of national identity. 6. Findings on Social Cohesion 6.1 The findings based on data obtained using the country specific scale on social cohesion point to some significant school system related factors that constrain the achievement of educationally relevant goals of national cohesion, national integrity and national unity. 6.2 There is significant inadequacy of and disparities in opportunities, for second language learning, for students from the different ethnic groups to learn together, to exchange ideas, for more informal interactions and cultural exchanges that foster mutual understanding. 6.3 A polarization of attitudes based on ethnicity indicates that the school system has not been sufficiently proactive and effective in facilitating social cohesion through the various processes it has in its command to do so, such as providing equal opportunities for second language learning. 6.4 The majority of students however are positively oriented towards participation in processes that will contribute to social cohesion, if opportunities are provided in the school system. 6.5 The findings on gender rights and equality indicate that the vast majority of students in Sri Lanka take a firm positive stand on equal rights for men and women, when presented as ideals. However, when presented in contexts such as job scarcity, a partiality towards men on the part of males in particular is noted, as reported in the international CIVED study “a very substantial gender difference in support for women’s rights continues to exist” (p. 186). 6.6 A positive feature in the findings of the CESL study is that students stand by the rights of all citizens, irrespective of their ethnicity, particular status as internally displaced citizens or, as members of anti-democratic groups.